(untitled) (Texas Journal of Philology, Culture and History, 2024)
The article examines the issue related to the creation of control knowledge and the formation of the control system during the years of independence. The importance of openness and transparency in the formation of the control system in the implementation of public control is justified. The importance of arming the institutions of civil society with the knowledge of control activities in effective public control is shown